The future roles and functions of South African bank branch managers. - Buthelezi, Bheje Nkululeko Freedom (My University, 2011)
This study investigated perceptions of South African bank Branch Managers about their future role in the changing banking environment and the influence of demographics on these. A comparison of the perceptions of Branch and Area Managers was attempted. A questionnaire, with 21 variables, developed by Deng, Moutinho & Meidan (1991) was used to collect data First National Bank managers. The 215 responses received were subjected to mean score analysis, factor analysis, correlation analysis and Chi-square testing. The results confirmed that marketing activities would become important in the future role of bank Branch Managers, identified three dimensions for clustering the roles of future Branch Managers and found that the demographic features of branch managers would influence their perceived roles in the future. A low response rate from Area Managers prevented conclusive confirmation that their perceptions do not differ from branch managers’ perceptions.
MBA - WBS
Keywords: Banking